You "complete the square":
x² - 10x + 18 = 0
Normally, you would start by dividing everything by the leading coefficient (the coefficient of x²). However, that is 1, so there is no need.
Subtract the constant:
x² - 10x = -18
Divide the coefficient of x by 2, and square it. The reason that we do this is to make the left side a perfect square, in the form of x² + 2cx + a². The middle term is "2c" in that format, so divide by 2 and square it to find c² (your constant). Now, you add it to the x² + 2ax format that you have now on the left side to get x² + 2cx + c²:
2c = -10
c = -5
c² = (-5)² = 25
x² - 10x + 25 = 7
Now that you have x and c, you factor the left side into (x+c)²:
(x - 5)² = 7
Put it into (x - a)² + b format:
(x - 5)² = 7
(x - 5)² - 7 = 0
Since we made the original equation equal to 0, and this one equal to 0, we can make them equal to each other:
x² - 10x + 18 = (x - 5)² - 7
The format is (x - a)² + b, so extrapolate the a and b from your answer.
a= 5 (not -5)
b= -7
2007-06-03 08:19:55
·
answer #1
·
answered by someone 3
·
0⤊
0⤋
x^2 - 10x +18 = (x - a)^2 +b
x^2 -10x +25 -25 + 18= (x - a)^2 +b
( x^2 -10x +25 ) - 7 = (x - a)^2 +b
( x - 5 )^2 + ( -7 ) = (x - a)^2 +b
by comparing
a = 5 and b = -7
2007-06-03 08:38:26
·
answer #2
·
answered by muhamed a 4
·
0⤊
0⤋
This looks like completing the square.
We do that by taking half of b and squaring it.
-10/2 = -5
(-5)^2 = 25
(x^2 - 10x + 25) + 18 - 25 =
(x - 5)^2 - 7
a = 5 and b = -7
2007-06-03 08:12:15
·
answer #3
·
answered by TychaBrahe 7
·
0⤊
0⤋
x² - 10x + 18
= (x² - 10x + 25) - 25 + 18
= (x - 5)² - 7
a = 5
b = - 7
2007-06-03 10:44:07
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
x^2-10x + 18
Using the completing the square method:
ax^2-(b/2)x = ax^2-(b/2)x+(b/2)^2 - (b/2)^2
x^2-10x + (25) + 18 - 25
(x^2-10x+25)^2 + -7
(x-5)^2 + -7
a = 5
b = -7
2007-06-03 08:14:33
·
answer #5
·
answered by whatcanmaxdo4u?everythingupscant 3
·
0⤊
0⤋